ACUTE TOXICITY OF AMMONIA FOR SOFT CORAL Xenia umbellata (Lamarck, 1916): Toxicidade aguda de amônia para o coral mole Xenia umbellata (Lamarck, 1916) - Martins Busanello, Giovanni; Shizuo Owatari, Marco; Vieira Rodrigues, Ricardo; Yumi Tsuzuki, Mônica; Magnotti, Caio (Arquivos de Ciências do Mar, 2024)
Coral reefs are important ecosystems on the planet and provide a wide variety of ecosystem services that are extremely important for the development and survival of several species, including humans. The lack of information and knowledge about the influence of abiotic parameters on the physiology of marine cnidarians with ornamental potential has hampered the cultivation of coral species on a large scale in aquaculture. The objective of this work was to determine the median lethal concentration after 96 h (LC5096h) of nonionized ammonia (NH3-N) for the octocoral white pulse soft coral (Xenia umbellata) over a period of 96 h. Eighty colonies of X. umbellata coral were exposed to five different ranges of N-NH3 (0.0, 0.92, 3.87, 5.95, 8.46 or 10.18 mg L–1, all in triplicate. Tests were performed on a standard semistatic system with 100% daily water renewal. The LC5096h was estimated to be 0.28 mg NH3-N L–1 (0.22~0.36mg L–1). The lethal concentration of ammonia decreased with increasing time. Furthermore, concentrations below 0.96 mg L –1 total ammonia (0.08 N- H3) are not lethal for this organism in an exposure period of 96 h. Keywords: Aquaculture; Octocoral; Regenerative; White pulse soft coral.